Psychometric properties of the Spanish version of the Sexual Assertiveness Scale (SAS) - Sierra, Juan Carlos; Vallejo Medina, Pablo; Santos Iglesias, Pablo (Anales de Psicología / Annals of Psychology, 2010)
The construct of sexual assertiveness has been developed to further the understanding of the ability to initiate sexual activity, refuse unwanted sex and negotiate pregnancy and sexually transmitted diseases prevention, and consequently, explore healthy behaviours. Sexual Assertiveness Scale (SAS), which is an 18 items questionnaire that consists of three factors measuring Initiation, Refusal, and Pregnancy Sexually Transmitted Disease prevention (P-STD) assertiveness. In this study, 853 people an- swered to the SAS together with others scales. The mean of the items has been similar to the theoretical average of the questionnaire. Moreover, the standard deviation has been close to one. Most of the items have showed a discrimination index higher than .30. No alpha increase has been ob- served if any item were deleted. Exploratory factor analysis showed three dimensions (48% variance) which replicate the original solution identically (Initiation ω = .80; Refusal ω = .76 and P-STD ω = .85). The scale dimen- sion has been confirmed by using a Structural Equation Modeling and found a good fit index. Significant correlations have been observed be- tween SAS and other related constructs.